Chapter Maritime Networks and Premodern Conflict Management on Multiple Levels. The Example of Danzig and the Giese Family - Wubs-Mrozewicz, Justyna (Atti delle «Settimane di Studi» e altri Convegni, 2019)
This article argues that a novel way to analyse maritime networks in premodern northern Europe is to trace the activities of people involved in conflict management. These people were traders, magistrates, judges, urban diplomats: sometimes all comprised in one person or a family. Specifically, if we take the Hanseatic city of Danzig and the Giese family as an example, it becomes apparent that these 'conflict managers' operated on various levels: the city, the region, the state, the Hanse and on the level of politics and economic policy between states and cities. Economic interests and conflicts were intertwined with political, social and cultural matters, and should be investigated together.